2020
DOI: 10.3892/mmr.2020.11472
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‑based proteomic analysis reveals potential regulatory networks in dust mite‑related asthma treated with subcutaneous allergen immunotherapy

Abstract: asthma is one of the most common childhood chronic diseases worldwide. Subcutaneous immunotherapy (SciT) is commonly used in the treatment of house dust mite (HdM)-related asthma in children. However, the therapeutic mechanism of SciT in asthma remains unclear. The present study aimed to investigate the molecular biomarkers associated with HdM-related asthma in asthmatic children prior and subsequent to SciT treatment compared with those in healthy children via proteomic analysis. The study included a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The non-invasive biofluid may SERPINs are serine protease inhibitors associated with the fibrinolytic system and have been identified as implicated in mucous production, potentially involved in the development of asthma. 28,29 SERPINB7 is essential for stabilizing epidermal strength and integrity. 30 Indeed, a genome-wide meta-analysis of 796,661 individuals, including 22,474 with atopic dermatitis, indicated that SERPINB7 mutations may play a role in the development of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The non-invasive biofluid may SERPINs are serine protease inhibitors associated with the fibrinolytic system and have been identified as implicated in mucous production, potentially involved in the development of asthma. 28,29 SERPINB7 is essential for stabilizing epidermal strength and integrity. 30 Indeed, a genome-wide meta-analysis of 796,661 individuals, including 22,474 with atopic dermatitis, indicated that SERPINB7 mutations may play a role in the development of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…the SERPINC1 gene encodes antithrombin III, which inhibits clotting factors; variations in its level may induce thrombosis or pulmonary embolism [ 88 ];…”
Section: Discussionmentioning
confidence: 99%
“…FN1 is a fibroadenoma protein involved in cell adhesion and migration. This may affect wound healing and the host immune system [ 18 ]. Since it is a glycoprotein involved in cell adhesion and migration, it is thought to be associated with signaling pathways related to cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%